Characteristics and outcomes of cubital tunnel decompression in diabetic patients receiving glucagon-like peptide-1 receptor agonists - Roban Shabbir; Simran Shamith; Paulo E. L. Parente; Luke Nicholson; Azad Ali (Clinics in shoulder and elbow, 2025)
Background: Cubital tunnel release (CuTR) relieves ulnar nerve compression; however, about 35% of patients who undergo this procedure develop persistent neuropathy and about 7% require revision. Type 2 diabetes mellitus (T2DM) worsens ulnar neuropathy, whereas glucagon-like peptide-1 receptor agonists (GLP-1 RAs) may be neuroprotective. We compared short- (90-day) and mid-term (2-year) CuTR outcomes in diabetic patients who did or did not receive perioperative GLP-1 RA treatment.Methods: TriNetX identified adults (≥18 years) with T2DM who underwent primary CuTR during the period 2015–2023, and who underwent at least 2 years of follow-up. The experimental cohort had received an active GLP-1 RA prescription at surgery, while the controls had not. Exclusion criteria were T1DM, pancreatitis, multiple endocrine neoplasia 2, systemic steroids, end-stage renal disease, or prior major CuTR. Propensity-score matching (1:1) balanced demographics, body mass index, glycated hemoglobin (HbA1c), creatinine, and comorbidities. Outcomes were captured using International Classification of Diseases, 10th Revision, Clinical Modification (ICD-10-CM) and Current Procedural Terminology (CPT) codes.Results: After matching, 1,766 pairs of patients (mean age, 58 years; 46% female) were analyzed. At 90 days, fewer GLP-1 RA users had emergency-department visits than non-users (8.9% vs. 10.7%, P=0.048). Despite higher HbA1c at each timepoint, GLP-1 RA users showed a larger decline. At 2 years, GLP-1 RA exposure was associated with fewer reoperations (5.2% vs. 6.9%, P=0.028), less frequent neuropathy (23.4% vs. 30.4%, P<0.001), and fewer inpatient admissions (14.6% vs. 17.2%, P=0.030). Major medical complications did not differ in occurrence between the groups.Conclusions: Perioperative GLP-1 RA therapy in diabetic patients undergoing CuTR correlated with fewer 90-day emergency visits and lower 2-year risks of revisional surgery and ICD-coded ulnar neuropathy (all-cause, non-adjudicated).. These findings support a potential protective role of GLP-1 RAs in this surgical population. Evidence: III. KCI Citation Count: 0